Social media skepticism and belief in conspiracy theories about COVID-19: the moderating role of the dark triad - Ashraf, Sadat Ahabdzadeh; Ong, Fon Sim; Wu, Shin Ling * (Springer Verlag (Germany), 2023)
The prevalence of conspiracy theories about COVID-19 in the wide-open social media environment has raised considerable concerns about the adverse effects of believing such theories. The previous work showed that skepticism is negatively associated with acceptance of media content. However, this association has yet to be investigated between skepticism towards content on social media and conviction of COVID-19 conspiracy theories. Furthermore, this association can be a function of social media users' dark triad traits comprising Machiavellianism, narcissism and psychopathy. A convenient sample of 439 Malaysian young adult social media users was recruited to complete the survey. Results showed that skepticism has a negative relationship with belief in conspiracy theories about COVID-19. However, the strength of the relationship is varied depending on respondents' Machiavellianism and narcissism levels. The negative association between skepticism and belief in COVID-19 conspiracy theories is weaker for individuals with high scores on Machiavellianism. High and moderate scores on narcissism were also found to diminish the negative relationship of skepticism with COVID-19 conspiracy ideation. The results yield implications for enhancing healthy skepticism to mitigate belief in conspiracy theories promulgated on social media. Nonetheless, Machiavellianism and narcissism appeared to weaken the power of skepticism on conspiracy theories.